2017
DOI: 10.11606/s1518-8787.2017051000315
|View full text |Cite
|
Sign up to set email alerts
|

Public policies on healthcare-associated infections: a Brazil and UK case study

Abstract: To summarize the historical events and drivers underlying public policy for the prevention and control of healthcare-associated infections in Brazil and in the United Kingdom. In doing so, the article aims to identify lessons and recommendations for future development of public policy. The analysis is based on a historical overview of national healthcare-associated infections programs taken from previously published sources. Findings highlight how the development of healthcare-associated infections prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
4
0
6
Order By: Relevance
“…Although Brazil has made considerable progress regarding healthcare prevention programs in the last two decades, structure fragilities remain (7) . Government systems of epidemiological surveillance have been introduced, but they still need to be improved (8) . According to data from the latest prevalence study conducted in Brazil, roughly 1 out of every 10 patients admitted to hospital will be affected by HAIs (9) .…”
Section: Characteristics Of Healthcare-associated Infectionsmentioning
confidence: 99%
“…Although Brazil has made considerable progress regarding healthcare prevention programs in the last two decades, structure fragilities remain (7) . Government systems of epidemiological surveillance have been introduced, but they still need to be improved (8) . According to data from the latest prevalence study conducted in Brazil, roughly 1 out of every 10 patients admitted to hospital will be affected by HAIs (9) .…”
Section: Characteristics Of Healthcare-associated Infectionsmentioning
confidence: 99%
“…Healthcare-associated infections (HAI) are a public policy concern in low-and middle-income countries, particularly in terms of providing technological support and qualified human resources, as well as improving antimicrobial stewardship programs and reducing the rates of microbial resistance [1]. Studies have shown that, in Brazil, the prevalence of HAIs in hospitals is 10.8% and pneumonia is the most common HAI [2].…”
Section: Introductionmentioning
confidence: 99%
“…7 In the years immediately prior (2003)(2004)(2005), the Brazilian Program of Infection Control was restructured, and some states started reporting surveillance data. 8 More information about HAIs was available than ever before, as the country underwent a period of economic development and political stability during this time. Finally, in those years, the first demands for public disclosure of individual hospitals' HAI rates were made by consumer protection organizations.…”
mentioning
confidence: 99%